PENGARUH PENDIDIKAN TEMAN SEBAYA BERBASIS GENRE KIT DIBANDING MODUL TERHADAP PENINGKATAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI REMAJA DI KOTA CIREBON - Lisnawati Lisnawati (Jurnal Medikes (Media Informasi Kesehatan), 2021)
Reproductive health education is an effort to prevent sexual deviations. Lack of knowledge is one of the factors that influence the high cases of deviant sexual behavior. The use of appropriate and attractive methods and media will be more effective in increasing knowledge. Learning while playing using the Genre Kit media will be an alternative in increasing student knowledge, especially about reproductive health. Research Objectives: Knowing the effect of Genre kit compared to modules in increasing knowledge about Adolescent reproductive health in Cirebon City in 2018. This type of research is a quasi-experimental design with pre-test post test with control group design. The use of samples using purposive sampling techniques. The number of samples was 40 teenagers, 20 teenagers from the intervention group, and 20 teenagers from the control group. Normality test, paired t-test, Wilcoxon and Mann-Whitney. There was no difference in the use of Genre Kit and modules to increase knowledge about adolescent reproductive health. The mean increase in knowledge in the Genre kit group was greater than 2.96 and p-value 0.413 (p> 0.05). There was no significant difference between the Genre kit media and modules in increasing knowledge about adolescent reproductive health.